Translating Batak Toba Cultural Terms in Toba Dreams:Domestication and Foreignization in English Subtitles - Ucok simamora; Daniel Sbastian (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
As Indonesian films increasingly reach international audiences through global streaming platforms, subtitle translation plays an important role in representing local cultural identity across languages. However, limited studies have examined how subtitle translation strategies shape the representation of indigenous cultural identity in audiovisual media. This study investigates the domestication and foreignization strategies used in translating Batak Toba culturally specific items (CSIs) in the English subtitles of Toba Dreams (2015). Guided by Venuti's (1995) domestication and foreignization framework and Newmark's (1988) cultural taxonomy, this study employed a descriptive qualitative approach using the official Netflix subtitle corpus. The findings identified 26 culturally specific items distributed across five cultural categories. Domestication was the dominant strategy (77%), particularly for Social Culture items, while foreignization (23%) was mainly applied to Material Culture items supported by visual context. Although domestication improved subtitle readability, it also reduced the representation of Batak Toba social hierarchy, especially the Dalihan Na Tolu kinship system. This study contributes to audiovisual translation research by demonstrating how subtitle translation strategies influence the representation of indigenous cultural identity while balancing cultural preservation and audience accessibility.